Pemberdayaan Masyarakat Melalui Pengolahan Singkong menjadi Bahan Baku Produk Olahan Makanan di Desa Tarung Manuah, Kecamatan Basarang, Kabupaten Kapuas - Titin Apung Atikah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Cassava is a type of plant that is easy to grow in various types of soil, and its cultivation method is relatively easy. The stems, leaves, and tubers of cassava have various benefits for human life. Limited knowledge and skills regarding the diversification of cassava-based processed products are an obstacle for which solutions must be sought. The purpose of this service activity is to empower the community, especially partners/target groups, through training on processing cassava into raw materials for processed food products. Community service activities carried out using training/mentoring and demonstrations/practices are one of the solutions that can be carried out for community empowerment. The results of community service activities show that all participants (100%) can actively participate in receiving all the knowledge and skills transferred and are interested in doing it themselves at home (100%). Processed products in the form of cassava flour will be consumed by themselves (77%) and sold (23%) with processed food products of cassava lunkhead (89%) and cassava noodles (11%), which were of high interest. This data shows that community service activities carried out by Palangka Raya University can contribute and become a solution to overcome problems faced by the community.